Manajemen Kelas Berbasis Gender (Segregasi Kelas) dalam Membentuk Karakter Siswa - Pujiono; Nafiisa Nurshabiika (ANNAHDLIYAH, 2026)
The aims of this study are (1) To describe the implementation of class segregation at SMP Islam AlMaarif 01 Singosari. (2) To describe student interaction when class segregation is implemented at SMP Islam AlMaarif 01 Singosari. (3) To describe the character of students when class segregation is implemented at SMP Islam AlMaarif 01 Singosari. This study uses a qualitative approach with descriptive research, which defines qualitative methods as research procedures that use descriptive data in the form of written or spoken words from people, images, and observed behavior. Data collection techniques use observation, in-depth interviews, and documentation. The results of this study indicate that classroom management based on gender can help shape student character, such as increasing self-awareness of boundaries between males and females, developing social skills, and improving academic achievement. However, this study also found that class segregation can create several obstacles, such as difficulties in developing communication skills between male and female students.